The best kept secret : single black fathers - Coles, Roberta L. (Rowman & Littlefield Publishers, 2009)
The Best Kept Secret studies the often-overlooked group of single, African American custodial fathers. While the media focuses on the increase of single mothers and the decline in marriage in the black community, Roberta Coles paints a nuanced picture of single black dads. Based on qualitative research, the author looks at the parenting experience of these fathers, who may have become single parents through nonmarital births, divorce, widowhood and adoption. The fathers, ranging in age from 20 to 76, discuss their motivations for taking custody of their children, what roles they enact as paren.